Policy Implementation of The Climate Village Program (Proklim) in Cisaranten Kulon Urban Village, Arcamanik Sub-District, Bandung City - mahpudin; M. Ridwan Caesar (GoResearch - Research & Publishing House, 2026)
The Climate Village Program (ProKlim) is a national government initiative implemented at the local level to address climate change impacts through community-based adaptation and mitigation. Cisaranten Kulon Urban Village, Arcamanik Sub-District, Bandung City, is one of the areas designated for ProKlim implementation. However, the implementation of this program has encountered several challenges, including limited human and financial resources, low levels of community participation, insufficient technical assistance from the Environmental Agency (DLH), a budget that relies heavily on community contributions, and the absence of a formal Letter of Task that regulates the division of roles and responsibilities among program administrators. This study aims to describe the implementation of the Climate Village Program in Cisaranten Kulon Urban Village, identify obstacles encountered during policy implementation, and analyze the efforts undertaken to address these challenges. The analysis is based on the policy implementation theory of George C. Edward, which emphasizes four key indicators: communication, resources, disposition, and bureaucratic structure. A qualitative research approach was employed, with informants selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that the implementation of ProKlim in Cisaranten Kulon has been carried out but remains suboptimal. Program socialization has not fully reached all community members, resulting in limited public understanding of concrete implementation measures. Limited technical guidance from DLH has required local administrators to manage program activities independently. Budget constraints have restricted the scale and continuity of activities, while the absence of a formal Letter of Task has weakened coordination and clarity of responsibilities among stakeholders. Efforts to overcome these challenges include providing incentives for program administrators, strengthening collaboration with universities and environmental communities, seeking support through corporate social responsibility (CSR) schemes, and coordinating with DLH to clarify roles and responsibilities through the issuance of a formal Letter of Task.